Precision Multi-Forage Nutrition as a Driver of Sustainable Goat Agribusiness Performance - Nicholas Renaldo; Jahrizal Jahrizal; Achmad Tavip Junaedi; Suhardjo Suhardjo; Onny Setyawan; Sulaiman Musa; Cecilia Cecilia (Journal of Applied Business and Technology, 2026)
Feed cost remains the largest expenditure in goat farming enterprises and significantly influences profitability, competitiveness, and long-term sustainability. Despite advances in precision livestock farming, limited studies have examined precision nutrition from an agribusiness perspective, particularly in tropical goat production systems. This study aims to analyze the role of Precision Multi-Forage Nutrition (PMFN) as a driver of sustainable goat agribusiness performance through the strategic integration of seven functional forage crops: Bonanza maize (Zea mays), Sweet Lady maize (Zea mays), Indigofera zollingeriana, Anaphalis javanica, Medicago sativa, Pakchong grass (Pennisetum purpureum × Pennisetum americanum), and Odot grass (Pennisetum purpureum cv. Mott). Using a descriptive case study approach combined with techno-economic and agribusiness feasibility analyses, the study evaluates the nutritional, operational, and economic contributions of diversified forage resources within integrated goat farming systems. The findings indicate that the PMFN framework enhances feed security, improves resource utilization efficiency, reduces dependence on external feed markets, and strengthens business resilience. The integration of seven complementary forage species creates a balanced nutritional ecosystem that supports productivity while simultaneously optimizing feed costs and improving profitability. Guided by the Resource-Based View (RBV), the study demonstrates that diversified forage resources can function as valuable, rare, inimitable, and non-substitutable strategic assets that contribute to sustainable competitive advantage. Furthermore, the study introduces the concept of Forage-Based Competitive Advantage (FBCA), which positions forage diversity and precision nutrition as strategic drivers of agribusiness performance rather than merely production inputs. The results suggest that Precision Multi-Forage Nutrition represents a transformative agribusiness innovation capable of enhancing economic sustainability, operational resilience, and long-term competitiveness in goat farming enterprises. These findings provide theoretical contributions to agribusiness strategy literature and practical implications for farmers, investors, and policymakers seeking sustainable livestock development models.